Penggunaan Media Pembelajaran Geogebra Terhadap Hasil Belajar Siswa Tentang Materi Program Linier Kelas X - Arif Sunaryo (Departement of Mathematics Education, 2020)
This study aims to examine whether the use of instructional media with Geogebra can improve student learning outcomes about linear level vocational program material. The object in this study was students of class X-Catering 1 SMK Negeri 1 Soreang. The method used is a classroom action research, which consists of 2 (two) cycles based on the syllabus of teaching mathematics teachers in class X SMK. Each cycle is carried out in accordance with the changes to be achieved. In this case the student learning outcomes of the passing grade minimum completeness criteria (KKM).